Pengaruh Konsentrasi Natrium sitrat dan Variasi Prapemasakan Terhadap Karakteristik Multigrain Rice Instan - Elly Kurniawati; Laras Dwi Hartanti (Politeknik Negeri Jember, 2023)
Instant multigrain rice is instant rice with a combination of more than one type of rice, beans and grains. The study aimed to determine the effect of variations in precooking and the addition of sodium citrate on the physicochemical characteristics of instant multigrain rice. The research method used a combination of two factors, namely a combination of preprocessing (roasting and steaming) and sodium citrate concentration (2% and 5%). Data analysis used ANOVA at the 0.05% level. This study included preparation of ingredients, weighing of ingredients, size reduction of edamame and kidney beans, washing, soaking (Na3C6H5O7 2% and 5%), washing, precooking (roasting and steaming), cooking, cooling, freezing, thawing, drying, and rehydration. Variations in the preprocessing method and the addition of sodium citrate concentration had a significant effect on the value of water content, fiber content, protein content, fat content, color and rehydration time. The value of water content obtained ranges from 3.47%-5.03%, fat, 3.53%-4.09%, fiber 5.07%-5.51%, protein 12.23%-12.79, rehydration time 5.07-5.51 minutes and color obtained brightness value (L*) of 53.22%-53.79%, reddish value (a*) 7.08%-6.53%, and yellowish value (b*) 14.22%-14.81%.